Survey of Routing Protocols in MANET (International Journal of Engineering and Computer Science, 2018)
MANET is set of different types of mobile node. MANET is mobile so they utilize wireless connection to attach with network. MANET can be deployed at low cost in variety of application. In MANET different types of routing protocols have been recommended. These protocols can be classified into three main categories reactive (on-demand), proactive (table-driven) and hybrid routing protocols namely AODV, OLSR and ZRP. This paper focus on the survey of reactive, proactive and hybrid routing protocols